Solusi Menghidupkan Kembali Pendidikan Surau - Yusran Ilyas (STIT Muslim Asia Afrika, 2022)
This paper discusses the solution to rebuild surau education in Minangkabau. The crediting of the surau function occurs from time to time. In the 17th to 18th centuries, surau became the center of gravity of the community so that the development of an area was determined by the existence of surau. In stark contrast to the time of the Dutch East Indies Government until now, surau is nothing more than a place of worship and a place of recitation that is held periodically, and its function as a machine of knowledgeable people has been replaced by modern schools. At least, this old-style surau education is maintained because there a person's character, independence, and personality are formed. This special value is the reason for restoring surau as an educational institution for the development of quality human beings. Because the times have changed, the surau must be able to adjust to the situation to be able to survive. To find a way out in rebuilding surau, historical science is used that photographs the state of surau over time and its causality with the changing times. This science will show the factor of weakening and strengthening surau so that this will give rise to alternative and solutive ideas to form adaptive surau education.